Efektifitas Penggunaan Sentra Imtaq Dalam Pembelajaran Sirah Nabawiyah Bagi Anak Usia Dini - Salis Hijriyani, Yuli (ACIECE, 2018)
Sirah nabawiyah is the life journey of Prophet Muhammad in conveying and manifesting islamictreatises for human life. Learning sirah nabawiyah is the first step to love God by following anddoing His messenger’s sunnah. Sirah nabawiyah is part of the source of islamic law and the bestmeans to find uswatun hasanah for a child’s life. Therefore, learning sirah nabawiyah for earlychildhood is so very important to be delivered pleasantly that a child can understand it easily.One of the learning ways is by using a certain kind of learning center, namely the center ofImtaq. Sirah nabawiyah learning can be succesful with the support of educational toys andgames that can be played by child’s in Imtaq center. The internalization of religious valuesthrough the educational toys and games can form well understanding of sirah nabawiyah. As aresult, a child’s achievement in knowing His God and knowing the prophet and the messengersare the indicators of his well sirah nabawiyah learning in using Imtaq center effectively